Self‐Rolled Porous Hollow Tubes Made up of Biodegradable Polymers. Issue 10 (15th March 2017) - Peng, Ling; Zhu, Jian; Agarwal, Seema
Abstract : Tubular porous scaffolds of biodegradable polymers are made by self‐rolling of a 2D membrane in water without use of any classical thermo‐/pH‐responsive polymers in few minutes. The tubes have a gas permeable wall, allowing the flow of water (10 cm s −1 ) without leakage, good mechanical properties, and are stable in water at all temperatures once they are formed. Abstract : A tubular highly porous scaffold of polylactide (PLA) and poly‐ε‐caprolactone (PCL) is fabricated by self‐rolling of a 2D fibrous bilayer of PLA and PCL in water without use of any classical thermo‐/pH‐responsive polymers. The self‐rolling and diameter of the tube are dependent upon the bilayer thickness and temperature. A 75 µm thick 2D bilayer (PLA = 25 µm; PCL = 50 µm) rolls to a hollow tube of diameter around 0.41 mm with multilayered wall at 40 °C within 5 min. The tubes keep their form and size in water at all temperatures once they are formed. The interesting properties of the hollow tubes, that is, permeation of gases through the walls and flow of water without leakage under tested conditions in combination with good mechanical stability, use of only biodegradable polymers, and easy and reproducible fabrication method, allow them to be promising candidates for future studies as scaffolds for tissue engineering.